SOCIAL MEDIA MARKETING TRENDS: INFLUENCERS' ACCOUNTS FOR SMES PRODUCT MARKETING - Erwin Erwin; Elia Ardyan; Sinar Dharmayana Putra (International Journal of Economics, Business and Accounting Research (IJEBAR), 2022)
The existence of influencers' accounts on social media is utilized in public relations initiatives to position business products so that they can contribute to marketing performance. Therefore, this study aims to analyze the effect of using influencers’ accounts on marketing performance for SMEs actors. The participants were 226 SMEs actors using social media who were collected using a questionnaire and the scale used was the Likert Scale (5 Scale). The data obtained were analyzed using Partial Least Square Structural Equation Model (PLS-SEM) and processed using WarpPLS Version 8.0. Based on the results gained; it is recommended that the use of influencers’ accounts on social media has a significant positive influence on the marketing performance of SMEs. The influencers could directly trigger good marketing performance and the use of influencers mediated by product positioning customized with certain types of products could also have a significant positive influence on the marketing performance of SMEs.